Conflict of Pragmatic Principles in the Arabic Conjunction “Wa”: A Corpus-Based Study - Wali, Abdul; Sulistyowati; Ibtisam (Jurusan Pendidikan Bahasa Arab, 2024)
The conjunction wa (الواو) in Arabic is a coordinating conjunction that connects words with words, phrases with phrases, or clauses with clauses. However, the conjunction wa is different from other conjunctions because it has different uses, that is, it has different meanings according to its grammar, resulting in a conflict of pragmatic principles. In this research, researchers used a corpus linguistics-based approach, namely collocation analysis (words that appear together) and concordance (contextual) data, data obtained from the Arabic Sketch Engine corpus. Then the researcher noted important things regarding the function of the conjunction wa according to early (classical) Arabic language experts which are not found in modern Arabic. The conjunction wa is divided into two parts, namely: wa 'amilah (wa which cannot be in one word by itself) and wa ghiru 'amilah (wa which can stand alone). From the top 20 data taken from the Sketch Engine Arabic language corpus, there are several functions of the conjunction wa in a sentence including: 14 as the conjunction wa ‘athaf, 5 as the conjunction wa isti'nafiyah/ibtidaiyah, and 1 as the conjunction wa hal. From the overall data it can be concluded that the majority of wa conjunctions function as wa ‘athaf, namely connecting nouns with nouns or verbs with verbs and so on.